Rancang Bangun Sistem Informasi Pengenalan Kebudayaan Kabupaten Nagekeo Berbasis Web - Charles Angi; Lambang Probo Sumirat; Budi Santoso (STMIK Banjarbaru, 2025)
The E'tu tradition, a customary boxing ritual in Nagekeo Regency, holds high cultural value but is gradually being forgotten due to the lack of digital documentation. This scarcity creates difficulties in accessing information about its history, meaning, and ritual procession, particularly for the younger generation and outsiders. This study aims to develop a web-based information system to introduce and preserve the E'tu ritual. The method employed is the Waterfall model, which encompasses requirements analysis, system design, implementation, testing, and system maintenance. Development is carried out using the Laravel framework with PHP as the programming language and MySQL as the database for structured data storage. Test results indicate that the system can effectively present historical information, meanings, processions, and visual documentation of the E'tu ritual in an easily accessible manner. Consequently, this platform supports the preservation of local culture while facilitating the dissemination of accurate information to both the younger generation and tourists, serving as a strategic step in promoting the cultural heritage of Nagekeo Regency in the digital era.Keywords: Information System; E'tu Ritual; Culture; Web; Laravel AbstrakTradisi E'tu, tinju adat di Kabupaten Nagekeo, memiliki nilai budaya tinggi namun mulai terlupakan karena minimnya dokumentasi digital. Hal ini menyebabkan kesulitan akses informasi mengenai sejarah, makna, dan prosesi ritual, terutama bagi generasi muda dan masyarakat luar. Penelitian ini bertujuan mengembangkan sistem informasi berbasis web untuk memperkenalkan dan melestarikan ritual E'tu. Metode yang digunakan adalah model Waterfall yang meliputi analisis kebutuhan, perancangan, implementasi, pengujian, dan pemeliharaan sistem. Pengembangan dilakukan dengan framework Laravel menggunakan bahasa PHP dan basis data MySQL untuk penyimpanan data secara terstruktur. Hasil pengujian menunjukkan bahwa sistem mampu menyajikan informasi sejarah, makna, prosesi, dan dokumentasi visual ritual E'tu dengan mudah diakses oleh masyarakat. Dengan demikian, platform ini mendukung pelestarian budaya lokal sekaligus memudahkan penyampaian informasi yang akurat kepada generasi muda dan wisatawan, serta menjadi langkah strategis promosi warisan budaya Kabupaten Nagekeo di era digital.Kata Kunci: Sistem Informasi; Ritual E'tu; Kebudayaan; Web; Laravel